Direct access to pyrido/pyrrolo[2,1-b]quinazolin-9(1H)-ones through silver-mediated intramolecular alkyne hydroamination reactions - Wang, Hengshuai; Jiao, Shengchao; Chen, Kerong; Zhang, Xu; Zhao, Linxiang; Liu, Dan; Zhou, Yu; Liu, Hong (Beilstein Journal of Organic Chemistry, 2015)
We report a synthetic methodology for the construction of the fused heterocyclic compounds pyrido[2,1-b]quinazolin-9(1H)-ones and pyrrolo[2,1-b]quinazolin-9(1H)-ones through an AgOTf-catalyzed intramolecular alkyne hydroamination reaction. The methodology is applicable to a wide scope of substrates and produces a series of fused quinazolinone heterocycles in good to excellent yields.
Keywords: heterocyclic molecules; intramolecular alkyne hydroamination; silver

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2004)

(untitled) - Mhaske, S. B.; Argade, N. P. (Tetrahedron, 2006)

(untitled) - Amin, A. H.; Mehta, D. R. (Nature, 1959)

(untitled) - Al-Shamma, A.; Drake, S.; Flynn, D. L.; Mitscher, L. A.; Park, Y. H.; Rao, G. S. R.; Simpson, A.; Swayze, J. K.; Veysoglu, T.; Wu, S. T.-S. (J. Nat. Prod., 1981)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2008)

(untitled) - Liu, J.-F.; Ye, P.; Sprague, K.; Sargent, K.; Yohannes, D.; Baldino, C. M.; Wilson, C. J.; Ng, S.-C. (Org. Lett., 2005)

(untitled) - Mori, M.; Kobayashi, H.; Kimura, M.; Ban, Y. (Heterocycles, 1985)

(untitled) - Johns, S. R.; Lamberton, J. A. (Chem. Commun., 1965)

(untitled) - Kametani, T.; Loc, C. V.; Higa, T.; Koizumi, M.; Ihara, M.; Fukumoto, K. (J. Am. Chem. Soc., 1977)

(untitled) - Eguchi, S.; Suzuki, T.; Okawa, T.; Matsushita, Y.; Yashima, E.; Okamoto, Y. (J. Org. Chem., 1996)

(untitled) - Mhaske, S. B.; Argade, N. P. (J. Org. Chem., 2001)

(untitled) - Morris, R. C.; Hanford, W. E.; Adams, R. (J. Am. Chem. Soc., 1935)

(untitled) - Kametani, T.; Higa, T.; Loc, C. V.; Ihara, M.; Koizumi, M.; Fukumoto, K. (J. Am. Chem. Soc., 1976)

(untitled) - Severin, R.; Doye, S. (Chem. Soc. Rev., 2007)

(untitled) - Müller, T. E.; Hultzsch, K. C.; Yus, M.; Foubelo, F.; Tada, M. (Chem. Rev., 2008)

(untitled) - Alonso, F.; Beletskaya, I. P.; Yus, M. (Chem. Rev., 2004)

(untitled) - Hesp, K. D.; Stradiotto, M. (ChemCatChem, 2010)

(untitled) - Fürstner, A.; Davies, P. W. (Angew. Chem., Int. Ed., 2007)

(untitled) - Patil, N. T.; Yamamoto, Y. (Chem. Rev., 2008)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Wang, Y.; Rapakousiou, A.; Latouche, C.; Daran, J.-C.; Singh, A.; Ledoux-Rak, I.; Ruiz, J.; Saillard, J.-Y.; Astruc, D. (Chem. Commun., 2013)

(untitled) - Wong, V. H. L.; Hor, T. S. A.; Hii, K. K. (Chem. Commun., 2013)

(untitled) - Patil, N. T.; Singh, V. (J. Organomet. Chem., 2011)

(untitled) - Kinjo, R.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2011)

(untitled) - McNulty, J.; Keskar, K. (Eur. J. Org. Chem., 2014)

(untitled) - Müller, T. E.; Grosche, M.; Herdtweck, E.; Pleier, A.-K.; Walter, E.; Yan, Y.-K. (Organometallics, 1999)

(untitled) - Sevov, C. S.; Zhou, J.; Hartwig, J. F. (J. Am. Chem. Soc., 2014)

(untitled) - Hesp, K. D. (Angew. Chem., Int. Ed., 2014)

(untitled) - Nguyen, T. M.; Nicewicz, D. A. (J. Am. Chem. Soc., 2013)

(untitled) - Beauchemin, A. M. (Org. Biomol. Chem., 2013)

(untitled) - Minatti, A.; Muñiz, K. (Chem. Soc. Rev., 2007)

(untitled) - Banerjee, D.; Junge, K.; Beller, M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Kanno, O.; Kuriyama, W.; Wang, Z. J.; Toste, F. D. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ye, D.; Zhang, X.; Zhou, Y.; Zhang, D.; Zhang, L.; Wang, H.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2009)

(untitled) - Zhang, X.; Zhou, Y.; Wang, H.; Guo, D.; Ye, D.; Xu, Y.; Jiang, H.; Liu, H. (Green Chem., 2011)

(untitled) - Zhang, X.; Zhou, Y.; Wang, H.; Guo, D.; Ye, D.; Xu, Y.; Jiang, H.; Liu, H. (Adv. Synth. Catal., 2011)